2022
DOI: 10.1002/hbm.26164
|View full text |Cite
|
Sign up to set email alerts
|

Investigating cognitive neuroscience theories of human intelligence: A connectome‐based predictive modeling approach

Abstract: Central to modern neuroscientific theories of human intelligence is the notion that general intelligence depends on a primary brain region or network, engaging spatially localized (rather than global) neural representations. Recent findings in network neuroscience, however, challenge this assumption, providing evidence that general intelligence may depend on system‐wide network mechanisms, suggesting that local representations are necessary but not sufficient to account for the neural architecture of human int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 133 publications
1
4
0
Order By: Relevance
“…The theory further suggests that the manifestation of crystallized and fluid intelligence can be traced to the nature of connections within these networks—strong, stable connections and easy-to-reach brain states facilitate verbal intelligence, while weaker, more variable connections and hard-to-reach states might underpin nonverbal intelligence. The theory aligns with findings that associate efficient network reconfiguration with fluid intelligence, suggesting that the brain’s ability to transition between different network states in response to cognitive demands is a substrate of cognitive ability (Anderson & Barbey, 2023; Bassett et al, 2011; Dubois et al, 2018; Wen et al, 2015). Some recent studies, however, have found the opposite associations between brain reconfiguration and intelligence, namely the increased stability of brain networks was related to higher intelligence (Hilger et al, 2017, 2020; Pamplona et al, 2015; Thiele et al, 2022).…”
Section: Introductionsupporting
confidence: 83%
“…The theory further suggests that the manifestation of crystallized and fluid intelligence can be traced to the nature of connections within these networks—strong, stable connections and easy-to-reach brain states facilitate verbal intelligence, while weaker, more variable connections and hard-to-reach states might underpin nonverbal intelligence. The theory aligns with findings that associate efficient network reconfiguration with fluid intelligence, suggesting that the brain’s ability to transition between different network states in response to cognitive demands is a substrate of cognitive ability (Anderson & Barbey, 2023; Bassett et al, 2011; Dubois et al, 2018; Wen et al, 2015). Some recent studies, however, have found the opposite associations between brain reconfiguration and intelligence, namely the increased stability of brain networks was related to higher intelligence (Hilger et al, 2017, 2020; Pamplona et al, 2015; Thiele et al, 2022).…”
Section: Introductionsupporting
confidence: 83%
“…These findings emphasize the need for future research to examine how network topology and dynamics are altered by TBI. Recent research has highlighted the importance of global brain network topology for facilitating cognitive abilities, 73 consistent with the present findings. Executive dysfunction can be a pernicious consequence of TBI, 74 , 75 implicating alterations to network topology and dynamics in neurological sequela following mTBI.…”
Section: Discussionmentioning
confidence: 99%
“…In applying theory-driven functional brain link selection, we demonstrated that models trained with links between brain regions proposed in neurocognitive intelligence theories [PFIT: ( 13 , 15 ), MD: ( 14 , 38 ), LPFC: ( 39 )] only partly outperformed models trained with links between the same number of randomly chosen regions and performed significantly worse than models trained with all brain links ( 60 ), while performance generally improved with increasing numbers of links. Taken together, this suggests that links between theoretically proposed brain regions include important but not complete intelligence-predictive information.…”
Section: Discussionmentioning
confidence: 99%